Context process variables as accountability measures of achievement in High School algebra - Cruz, Manuel O. 1927- (1982)
The study looked into the context process variables and accountability measures of achievement in high school algebra. The objective of the study is to determine how institutional achievement level accounts for student achievement, how beliefs or learner's teacher description, or supervisor's or administrator's beliefs account for student achievement, and how teacher's or learner's or superviusor's time on tasks or how administrator's logistic support to instruction accounts for student achievement. The research, which demonstrates the significance of belief networks, time on tasks, logistic support to instruction and the impact of institutional achievement level to instructional developemnt, is an attempt to contribute something valid to the improvement of teaching, particularly in mathematics.
Thesis (Ph.D.)--University of the Philippines, Quezon City.
Keywords: Algebra -- Study and teaching